Toothbrush contamination in family members (2010)
ABSTRACT: Objective: The purpose of this study was to determine the bacterial contamination of toothbrushes in family members. Materials and Methods: One hundred and two healthy subjects were included in this descriptive study. Every individual was examined clinically and microbiologically using the CPITN index and collecting subgingival plaque samples. Each participant received a toothbrush for home use and after one month they returned it to the investigators. All toothbrushes were cultured to determine the presence of periodontopathic bacteria and enteric rods. Wilkoxon signed rank test and t student test (P 0.05) were used to compare differences in the subgingival microbiota and toothbrush contamination and CPITN index among family members. Results: A high proportion of toothbrushes resulted highly contaminated with enteric rods (P 0.001) compared to the subgingival environment where periodontopathic bacteria were more prevalent. The most frequent microorganisms found in toothbrushes used by parents and children for one month were Enterobacteriaceae, Pseudomonadaceae species (>50%) and Fusobacterium spp (30%). Conclusions: High levels of enteric rods were commonly detected in toothbrushes used for 1 month among members of the families. These opportunistic organisms may have an important role in oral infections including gingivitis and periodontitis. Monthly replacement or disinfection of the toothbrush can reduce the risk of bacterial transmission/translocation and thus diminish the incidence of bio lm associated oral diseases.